Pemanfaatan Media Permainan Edukatif Interaktif dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini: Tinjauan Literatur - Baik Nilawati Astini; Gunawan Gunawan; Nurhasanah Nurhasanah; Ika Rachmayani (Indonesian Journal of Teacher Education, 2021)
Cognitive development in early childhood serves as a critical foundation for academic readiness and logical thinking skills. This narrative literature review aims to analyze the use of interactive educational games, both conventional (manipulative play materials) and digital-based applications in stimulating early childhood cognitive development based on literature published up to mid-2021. Relevant articles were retrieved from Scopus, Google Scholar, IEEE Xplore, and indexed national journal portals. The review demonstrates that interactive educational games contribute positively to enhancing working memory, basic mathematics, early literacy, and learning motivation. However, their effectiveness is strongly determined by the quality of instructional design, guided play principles, developmental appropriateness, and adult facilitation. This study recommends integrating educational media dynamically with hands-on play while strictly adhering to child development principles.